2023
DOI: 10.7150/ijms.81078
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Lymphangiogenesis-Related Gene Signature can Predict Prognosis and Immunosuppressive Microenvironment in Patients with Clear Cell Renal Cell Carcinoma

Abstract: Background: Lymphangiogenesis represents a key event in the progression and metastasis of patients with clear cell renal cell carcinoma (ccRCC). Nevertheless, the prognostic value of lymphangiogenesis-related genes (LRGs) in ccRCC patients remains unknown. Method: Differential analyses were performed to identify differentially expressed LRGs between normal and tumor tissues. A univariate Cox analysis was performed to identify differently expressed LRGs associated with overall survival (OS). LASSO and multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…It has been shown that conventional TNM staging may be inaccurate in predicting the prognosis of ccRCC patients because it does not take into account the effect of gene expression on prognosis [29]. Many studies are currently trying to predict the prognosis of patients with ccRCC by establishing risk signatures based on the results of gene sequencing and combining them with clinical information [30][31][32]. But the overall efficiency of clinical translation is low.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that conventional TNM staging may be inaccurate in predicting the prognosis of ccRCC patients because it does not take into account the effect of gene expression on prognosis [29]. Many studies are currently trying to predict the prognosis of patients with ccRCC by establishing risk signatures based on the results of gene sequencing and combining them with clinical information [30][31][32]. But the overall efficiency of clinical translation is low.…”
Section: Discussionmentioning
confidence: 99%
“… [ 28 ] Lymphangiogenesis prediction model IL4, CSF2, PROX1 and TEK PD1 expression was higher in high-risk group Providing new ideas for the prognosis evaluation and treatment of ccRCC patients. [ 29 ] Prognostic model IRF6, TEK, PLCB2, ABCB1, TGFA, COL4A5, PLOD2 and TUBB6 Elevated expression of high-risk groups of PD1. To predict the clinical prognosis and the efficacy of immunotherapy in ccRCC patients.…”
Section: Role and Regulation Of Pd1/pd-l1 Pathway In Ccrccmentioning
confidence: 99%
“…Lymph Node Metastasis Associated Transcript 1 (LNMAT1) promotes lymphatic metastasis and acts as a potential therapeutic target for LN-metastatic bladder cancer therapy [ 26 ]. Vascular endothelial growth factor C (VEGF-C), interleukin-4 (IL-4), colony-stimulating factor 2 (CSF2), prospero homeobox 1 (PROX1), and TEK receptor Tyrosine Kinase (TEK) is significantly associated with lymph node metastasis in renal cell carcinoma (RCC) [ 27 , 28 ]. Collagen and calcium-binding EGF domain-1 (CCBE1) and neuropilin-2 (NRP2) promote lymphangiogenesis and lymphatic metastasis in CRC and can be used as therapeutic targets in CRC [ 29 31 ].…”
Section: Introductionmentioning
confidence: 99%